2015
DOI: 10.1080/09658211.2015.1061012
|View full text |Cite
|
Sign up to set email alerts
|

Music evokes vivid autobiographical memories

Abstract: Music is strongly intertwined with memories-for example, hearing a song from the past can transport you back in time, triggering the sights, sounds, and feelings of a specific event. This association between music and vivid autobiographical memory is intuitively apparent, but the idea that music is intimately tied with memories, seemingly more so than other potent memory cues (e.g., familiar faces), has not been empirically tested. Here, we compared memories evoked by music to those evoked by famous faces, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 57 publications
(72 reference statements)
8
100
1
3
Order By: Relevance
“…The older participants judged their personal memories to be as specific as the younger participants, but it should be noted that there are general shifts from episodic to semantic details in autobiographical memories with aging (Levine et al, 2002). Overall, these results are consistent with the frequency, durability, strength and rich content of autobiographical memories associated with music (e.g., Gabrielsson, 2001, 2011; Janata et al, 2007; Belfi et al, 2015). …”
Section: Discussionsupporting
confidence: 80%
“…The older participants judged their personal memories to be as specific as the younger participants, but it should be noted that there are general shifts from episodic to semantic details in autobiographical memories with aging (Levine et al, 2002). Overall, these results are consistent with the frequency, durability, strength and rich content of autobiographical memories associated with music (e.g., Gabrielsson, 2001, 2011; Janata et al, 2007; Belfi et al, 2015). …”
Section: Discussionsupporting
confidence: 80%
“…Further inconsistencies were noted, depending on the overall aims of the studies in question. For example, one study focused exclusively on the external event subcategory, whereas eight studies reported only the semantic Healthy adults (8) Aizpurua and Koutstaal (2010), Ally et al (2013), Barnier et al (2014), Belfi, Karlan, and Tranel (2016), Campbell, Nadel, Duke, andRyan (2011), Palombo, Alain, Soderlund, Khuu, and, Rudoy, Weintraub, and Paller (2009), and Sheldon and Chu (2017) Healthy ageing (4) Aizpurua and Koutstaal (2015), Ford, Rubin, and Giovanello (2014) (2008) Other (parietal lesions) (1) Berryhill, Phuong, Picasso, Cabeza, and Olson (2007) Paediatric (2) (2015), Nadel, Campbell, and Ryan (2007), and Rabin and Rosenbaum (2012) Healthy ageing (1) Baron and Bluck (2009) Medial temporal lobe lesions/epilepsy (1) Hornberger et al (2010) Neurodegeneration (5) subcategory. Within the latter eight studies, further variability was evident in that some studies focused only on semantic details and did not report total external details, whereas others adopted a modified scoring system wherein all details were classified as either episodic or semantic.…”
Section: Part 1 -Review Of Existing Abm Studies Using the Ai Methodsmentioning
confidence: 99%
“…In this area of research, a few studies have looked at the influence of the emotional characteristics of a cue on autobiographical memory in clinical samples (e.g., depression) and these studies are often limited to comparing the ability to access autobiographical memories in response to positive and negative cues (Dalgleish et al, 2007;Williams & Broadbent, 1986), making these investigations not well suited to examine the effect of emotional arousal. An effective method to systematically examine the effect of a cue's emotional valence and arousal on remembering is to use musical stimuli (Belfi, Karlan, & Tranel, 2016;Janata, 2009;Janata, Tomic, & Rakowski, 2007). Using musical cues, Schulkind and Woldorf (2005) examined the differential impacts of the valence and arousal levels of retrieval cues on the emotional content of recalled autobiographical memories.…”
Section: Emotional Retrieval Factors and Autobiographical Memorymentioning
confidence: 99%
“…Second, we assessed the relationship between cue and memory valence and arousal by collecting measures of event valence and arousal and relating this to the valence and arousal of the memory cue (Schulkind & Woldorf, 2005). Finally, we examined the quality of the memories by collecting ratings of memory content and experience that are known to vary with music-induced remembering (Belfi et al, 2016;Krumhansl & Zupnick, 2013). With respect to this final issue, we were specifically interested in examining how the emotional characteristics of the cue (valence, arousal) related to the experience of remembering, particularly how memory vividness related to aspects of the remembered event (i.e., the content of the memory) following on findings from Ford et al (2012) that indicates emotion enhances the richness (vividness) of remembering (see also Ochsner, 2000).…”
Section: Overview Of the Current Study And Predictionsmentioning
confidence: 99%